Protein supplementation of ammoniated wheat straw: effect on performance of beef cows - Fike, G.D.; Simms, D.D.; Brandt, Robert T., Jr.; Cochran, R.C.; Vanzant, E.S.; Kuhl, Gerry L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Mature, crossbred beef cows (n = 87 in 1990-91, n = 84 in 1991-1992) were used to determine the effects of protein supplementation to cows fed ammoniated wheat straw during late gestation. Treatments included: 1) Control (C) - no supplement, 2) Low Protein (LP) - 4.5 lb of a 10% crude protein (CP) supplement, 3) Medium Protein (MP) - 4.5 lb of a 20% CP supplement, and 4) High Protein (HP) - 4.5 lb of a 30% CP supplement. Supplementation increased weight gain over controls (P<.01). HP cows gained more (P=.05) weight than LP-supplemented cows and tended (P=.11) to gain more weight than MP-supplemented cows. Supplementation also increased body condition score (BCS, 1-9 scale) over control cows (P<.01), but no difference was noted among supplemented groups. From the end of the feeding period until weaning, cows previously supplemented lost more weight (P<.01) than controls and exhibited little change in BCS, whereas controls increased BCS by .5 during the same period. Calving dates, calf birth weights, calf weaning weights, calf average daily gain, percent of cows cycling prior to breeding, and percent of cows pregnant did not differ between treatments. Consequently, although additional protein increased weight gain prior to parturition, this response did not impact economically important traits.
Keywords: Beef; Ammoniation; Wheat straw; Protein supplementation; Beef cows